Presentation, management, and outcomes of orbital infections in patients with cancer - Niknahad, Ava; Gibbons, Alison B.; Ahmed, Aishah; Lee, Heya; Mehta, Setu; Al-Ali, Samir; Haile, Meron; Srikumar, Anjana; Stemme, Rachel; Suresh, Akanksha; Zhong, Justin C.; Woreta, Fasika; et al. (Frontiers in Ophthalmology, 2025)
PurposeThis study aimed to characterize the presentation, treatment, and outcomes of preseptal and orbital cellulitis in patients with and without cancer, to help guide management of these infections.MethodsA retrospective cohort study was conducted at a tertiary care center to identify adults who presented from 2007 to 2022 with orbital and preseptal cellulitis. Patients with cancer were defined as patients actively receiving chemotherapy or in remission but on immunosuppressants at the time of their orbital infection care. Their demographics, presentation, management, and follow-up characteristics were recorded. Management variables included data on antibiotics, antifungals, and systemic steroids administered.ResultsOf the 183 patients presenting with orbital cellulitis, 15 (8.2%) had active cancer while of the 130 patients with preseptal cellulitis, 8 (6.2%) had cancer (p = 0.661). Patients with cancer who were found to have preseptal cellulitis were more likely to have head and neck cancer than those who had orbital cellulitis (50.0 versus 0%, p = 0.008). In the orbital cellulitis cohort, the management of patients with and without cancer differed in antifungal and corticosteroid therapy. Compared to patients without cancer, patients with cancer received a higher antifungal rate (46.7% versus 10.1%, p = 0.001) and were started on steroids a median of 2 days later (3.0 versus 1.0 day after admission date, p = 0.007). Both cohorts had similar readmission rates (20.0% in cancer and 11.3% in non-cancer cohort, p = 0.397) and eye exam findings at follow-up. Patients with and without cancer in the preseptal cellulitis cohorts were similar in all characteristics assessed.ConclusionsPatients with cancer presenting with orbital cellulitis have a higher rate of antifungal administration and are started on systemic steroids later compared to patients without cancer, although they have similar eye exam outcomes and readmission rates. Patients with cancer are not at an increased risk of preseptal cellulitis and are managed similarly to patients without cancer.